The Contemporary Human Resources Function - Rodríguez-Fernández, María Mercedes; Bryan-Jiménez, Carlos (My University, 2017)
Abstract Current companies encounter important challenges day to day. Many factors such as the economic globalization, the change in the way of working, the Internet boom, and the importance that the service sector is experiencing nowadays influence the new society in which persons and businesses actually cope. Each of these contingencies obligates the Human Resource function to adapt to new organizational goals moulding their strategies and tactics to the in fashion topics. In this work we present the classical functions integrated in the Human Resources department constituting its base of performance. We also deal equally with the high performance practices and the importance that is acquiring the binomial human resources management strategies – business performance such as new tendencies applicable in this area.
Keywords: Recursos humanos; Human Resources; High-Performance Practices; Profitability